PHYTOSYNTHESIS AND CHARACTERIZATION OF SILVER NANOPARTICLES FROM RUELLIA TUBEROSA (L.): EFFECT OF PHYSICOCHEMICAL PARAMETERS - M. N. L. C, HARIKA; P, RADHIKA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The current study focused on synthesizing silver nanoparticles (AgNPs) using Ruellia tuberosa aqueous tuber extract (RTTE) and silver nitrate (AgNO3) solution. Methods: AgNPs were synthesized using an aqueous tuber extract of the medicinal herb R. tuberosa (L.). The existence of significant phytoconstituents involved in synthesizing the AgNPs was determined using the gas chromatography–mass spectrometry (GC–MS) study. We evaluated the physical and chemical parameters such as the effect of time, temperature, metal ion concentration, crude aqueous tuber extract concentration, and pH in the synthesis of nanoparticles. The AgNPs were characterized using ultraviolet (UV)–Vis spectroscopy, field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (EDX), high-resolution transmission electron microscope (HRTEM), selected area electron diffraction (SAED), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) techniques. Results: R. tuberosa tuber extract was rich in various phytochemical constituents which were identified by GC–MS. For biosynthesis, the optimal values were 1 mM AgNO3concentration, 0.1 mL of aqueous tuber extract, and a 40 min incubation temperature of 70°C. The existence of a characteristic surface plasmon resonance (SPR) peak at 421 nm indicated the biosynthesis of AgNPs using UV–Vis spectroscopy. At higher temperatures and alkaline pH, the development of AgNPs increased overtime and remained stable up to 4 weeks. FESEM, EDX, HRTEM, SAED, and XRD analysis revealed that most AgNPs were spherical, with an average size distribution of 34.9 nm and a crystalline phase, face-centered cubic lattice. Infrared (FTIR) spectroscopic analysis revealed that hydroxyl and amino functional groups were involved in the biosynthesis and stabilization of AgNPs. Conclusion: The synthesis of AgNPs from R. tuberosa aqueous tuber extract was a cost-effective process and environmental friendly.